From the Arctic to the Tropics: An Analysis of Food Security Strategy Variation in Small, Isolated, and Sheltered States - Valerie Lauren Hedges 1996- (2023)
Food is a vital resource for life for everyone. Secure access to it is a basic human right. Therefore, states are responsible for maintaining food security for their constituents. This thesis is aimed at discovering the causes of variation in food security strategies for small, isolated, and sheltered states. With a focus on the link between shelter and food security strategies, I will delve into the theories of shelter and securitization to explain possible causes of variation including but not limited to factors such as nutrition, health, economics, as well as cultural and societal influence. By focusing on small, isolated, and sheltered states like Iceland, Greenland, and Jamaica, we can envision three different approaches to food security strategies. This thesis will challenge the limits of shelter theory and look at how different small states utilize their shelter to optimize food security. By analyzing these variations, it is possible to discover the different views on successful food securitization. This thesis will ideally provide a foundational framework in which future researchers can further explain diversification in security, food or otherwise, in small states.